Pengaruh Tunneling Incentive Terhadap Tax Avoidance Dengan Koneksi Politik Sebagai Variabel Moderasi - Retnowati, Wulan; Muchlish, Monawar (Universitas PGRI Madiun, 2024)
This study aims to determine and examine the effect of tunneling incentive on tax avoidance wit political connections as a moderating variable. Population in this study using property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the period 2016-2020. The data used in this study are secondary data and sample selection through purposive sampling technique. This research is a type of quantitative research with multiple regression model. In addition, the regression analysis model used in this study moderated regression analysiss (MRA) using SPSS statistics 24 software. Based on the results of the analysis, it shows that tunneling incentive has no effect on tax avoidance. Political connection as a moderating variable has been shown to strengthen the effect of tunneling incentive on tax avoidance.